Synthesis, Characterization, and Theoretical Study of Some New Organotellurium Compounds Derived from Camphor - Nuha Hussain Al-Saadawy (Universitas Gadjah Mada, 2022)
The present work describes the synthesis of a variety of organotellurium compounds. The first part describes the synthesis of a new series of organotellurium compounds containing azomethine groups. Reaction of (E)-(4-((1,7,7-trimethyl bicyclo[2.2.1]heptan-2-ylidene)amino)phenyl)mercury(II)chloride and (E)-(5-methyl-2-((1,7,7-trimethylbicyclo[2.2.1]heptan-2-ylidene)amino)phenyl) mercury(II)chloride with tellurium tetrabromide in 2:1 mole ratio yielded the tellurated Schiff bases Ar2TeBr2 (where Ar = 1-(C9H16C=N)C=N)C6H4 and 1-(C9H16C=N)C=N)-4-CH3C6H3) respectively. Reduction of organyl tellurium dibromide Ar2TeBr2 by hydrazine hydrate obtained the corresponding tellurides (i.e., Ar2Te) in good yields. Characterization of the prepared compounds was carried out using infrared spectrum (FT-IR), proton nuclear magnetic resonance spectrum (1H-NMR), and elemental analysis (CHN). The molecular structure of the organotellurium compounds was investigated using the density functional theory with hybrid functional (B3LYP), and the basis set 6-31G Geometrical structure, HOMO surfaces, LUMO surfaces, and energy gap have been produced throughout the geometry optimization. The molecular geometry and contours for the organotellurium compounds were investigated throughout the geometrical optimization. The donor and acceptor properties have been studied by comparing organotellurium compounds' highest occupied molecular orbital energies (HOMO). The present study aims to prepare organotellurium compounds derived from aniline, p-toluidine, and camphor and their derivatives using tellurated Schiff bases.